Brothers, Sisters and Fictive Kin: Communication About Sex Among Urban Black Siblings. (September 2014) - Wallace, Scyatta A.; Hooper, Lisa M.; Persad, Malini
Siblings have been shown to influence youth substance use and violent behavior. However, limited research has examined sibling-influences on sexual activity, particularly among urban Black youth. The current qualitative research was an exploratory study to describe discussions among siblings about sex and sexual health. Individual interviews were conducted with 15 Black youth (7 male, 8 female) from New York City ages 16 to 19 years. Participants were recruited from community agencies serving low income youth. Results indicated that youth had discussions about sex with their siblings. Discussions among siblings included information about sex, conversations about sexual activities and advice about sexual relationships. Some gender differences were observed. Males reported feeling pressure from their male siblings to be engaged in sexual activity. Female youth discussed hearing HIV/AIDS prevention messages from their siblings. Findings highlight the important role that siblings may play in socializing urban Black youth regarding sexuality, sexual health, and HIV/AIDS prevention.